100 Books for Teachers of English as a Second Language An Annotated Bibliography - Springer, Hisami K., Comp.; Hawaii Univ., Honolulu ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1971)
This annotated bibliography includes materials for English as a second language published after 1960 which are available at the University of Hawaii libraries. Part 1 lists general works on methodology, testing, preparation and analysis of materials, and works for teacher training. Part 2 includes materials which concentrate on specific geographical areas. Pare 3 covers textbooks and Part 4 lists miscellaneous selected titles relevant to the field. Not included are reference sources such as guides to the literature, encyclopedias, bibliographies, printed library catalogues, dictionaries, indexing and abstracting services, current awareness services, and serial publications. (Author)
Microfiche.
Keywords: Annotated Bibliographies; Bibliographies; English (Second Language); Instructional Materials; Language Tests; Material Development; Resource Materials; Teacher Education; Teaching Methods